2013
DOI: 10.1080/19476337.2012.722687
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity ofVigna unguiculataL. walp and hard-to-cookPhaseolus vulgarisL. protein hydrolysates

Abstract: Recent research, using model systems, has shown that enzymatic hydrolysis of food proteins can make them act as direct scavengers of diverse free radicals. This study aimed at the characterization of protein hydrolysates with antioxidant properties from Vigna unguiculata L. walp and hard-to-cook Phaseolus vulgaris L. protein concentrates. The maximum values obtained for all the assays were 15.1 mM/mg of protein for Trolox-equivalent-antioxidative capacity, 98.2% for percentage of 2,2-diphenyl-1-picrylhydrazyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
4
14
1
3
Order By: Relevance
“…Mung bean albumin peptides showed high ferrous ion chelating activity, but low ABTS radical scavenging activity (Supplementary Materials Figure S1). The ferrous ion chelating activity of mung bean albumin peptides derived from pepsin-pancreatin enzymatic hydrolysis was found to be higher than the ferrous ion chelating activity of cowpea and common bean protein hydrolysates derived from the same enzyme scheme, as reported by Segura-Campos et al [36]. The ferrous ion chelating activity of mung bean albumin peptides was also found to be higher than the ferrous ion chelating activity of soybean lunasin, as reported by Garcia-Nebot et al [37].…”
Section: Discussionsupporting
confidence: 70%
“…Mung bean albumin peptides showed high ferrous ion chelating activity, but low ABTS radical scavenging activity (Supplementary Materials Figure S1). The ferrous ion chelating activity of mung bean albumin peptides derived from pepsin-pancreatin enzymatic hydrolysis was found to be higher than the ferrous ion chelating activity of cowpea and common bean protein hydrolysates derived from the same enzyme scheme, as reported by Segura-Campos et al [36]. The ferrous ion chelating activity of mung bean albumin peptides was also found to be higher than the ferrous ion chelating activity of soybean lunasin, as reported by Garcia-Nebot et al [37].…”
Section: Discussionsupporting
confidence: 70%
“…These amino acids have been reported to contribute to tyrosinase-inhibition and metal-chelating activity. 1,17,19,22,23,24,46…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have reported the tyrosinase-inhibitory effect and copper-chelating activity of proteins, protein hydrolysates, and peptides from natural sources such as rice bran, 2,16 silk, 17 sunflower, 18 zein, 19 chickpea, 20,21 cowpea, 22 and red seaweed. 23 Some synthetic short peptides appear to show inhibitory activity against tyrosinase.…”
Section: Introductionmentioning
confidence: 99%
“…Segura‐Campos et al . () studied the use of the mixture of Flavourzyme and Alcalase on the enzymatic hydrolysis of hard‐to‐cook bean protein concentrates and demonstrated that the combined use of these enzymes was able to increase the antioxidant activity of the hydrolysates.…”
Section: Resultsmentioning
confidence: 99%